Evaluation of pathological manifestations in buildings in terms of geographical orientation - Mazer, W.; Silva, L. M. R.; Lucas, E.; Santos, F. C. M. (Revista ALCONPAT, 2016)
In order to evaluate the incidence of pathological manifestations on the facades of buildings, correlated with the geographical location, 52 buildings for residential and commercial use were analyzed in this study; these were distributed in different parts of the city of Curitiba, Brazil. It was observed that all the buildings evaluated had some type of pathological manifestation, and 25 of these were present on the facades of the buildings. It was found that the pathological manifestations on the facades show up in different amounts and locations, having identified a relation with the variation of temperature and the direction of the wind in terms of geographical orientation. Keywords: durability; facade; geographical location; pathological manifestation.